PENERAPAN MODEL PEMBELAJARAN SOMATIS, AUDITORI, VISUAL, INTELEKTUAL (SAVI) PADA MATERI KOLOID UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK DI KELAS XI MIA SMAN 2 BANGKINANG KOTA - Ariani, Yunita; Rasmiwetti, Rasmiwetti; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research on the application of Somatic, Auditory, Visualization, Intellectual (SAVI) learning model is aimed to know the improvement of critical thinking ability of students in class XI MIA SMAN 2 Bangkinang Kota on colloidal material. This research method is experimental research with Randomized Control Group Prestest-Posttest design. The data collection instruments used through prerequisite data, pretest and posttet data are based on the H. Ennis indicator. Data analysis technique that is by normality test, homogeneity, hypothesis and improvement of critical thinking ability. Research shows that the application of learning model Somatic, Auditory, Visualization, Intellectual (SAVI) can increase students' critical thinking ability on colloid material in class XI MIA SMAN 2 Bangkinang Kota. Improved students' critical thinking skills are in the medium category with N-gain of 0.63.Key Words : SAVI Learning Model, Critical Thinking, Colloid.